Non-communicated rudimentary uterine horn pregnancy and uterine rupture: A case report. (June 2022) - Wang, Li; Ren, Songtao; Zhang, Yan; Liu, Wei; Shi, Wentian
Rudimentary uterine horn pregnancy is a rare and serious type of ectopic pregnancy and is hard to diagnose due to a lack of typical clinical symptoms at the early stage. A 35-year-old woman who was17 weeks pregnant and had a complicated history of infertility came to our hospital complaining of abdominal pain without vaginal bleeding. Computed tomography scan after 12 hours showed that her pregnancy was in the small cavity of a rudimentary uterine horn, which had ruptured. Noncommunicating rudimentary uterine horn pregnancy is an extremely rare form of ectopic gestation, and its diagnosis and management remain challenging. Nevertheless, physician awareness of various forms of unicornuate uteri and rudimentary uterine horn can save lives.